Socio-economic model of the new system of higher environmental education in Russia - Guslyakova, Alla V.; Isaev, Konstantin V.; Ledashcheva, Tatyana N.; Valeeva, Nailya G.; Guslyakova, Nina I. (Frontiers in Education, 2025)
IntroductionThe article covers the problem of a reforming system of higher environmental education in the Russian Federation. According to a special decree no. 343 “On some issues of improving the higher education system” in Russia signed by the President Vladimir Putin in May 2023, the country is currently facing the transformation of the levels of its higher education. A new basic and specialized university education is becoming on the agenda, including its environmental profile. The goal of this study is to evaluate and analyze the new system of higher environmental education in Russia from the perspective of its social and economic functioning by referring to the mathematical graph theory.MethodsGraphs have become an efficient and useful instrument of assessment of various scientific phenomena including the development of the socio-economic model of higher environmental education in the Russian state. A working hypothesis was introduced to debate on the issue of an efficacy of the academic and educational reforms at the country's university level of the environmental acquisition. In the end, the research suggests an opportunistic development of the reforming system of the higher environmental education in Russia on the terms of its economic, ecological, and social principles.ResultsThe results of the study have demonstrated that 89.1% of the respondents consider themselves environmentally friendly people striving to follow the principles of sustainable development in the modern world. Simultaneously, almost 94% of young people surveyed believe that university students should be environmentally active and help their university build a more sustainable and healthy academic and research environment. Statistical data in the analyzed graph G has showed the maximum sums of weights on the nodes which reflect the indicators of domestic state policy (20.84); foreign state policy (21.4); demands for environmental specialists in the world (21.01); environmentally caused diseases in Russia and the world (16.00); the knowledge of foreign languages as a tool that expands general educational horizons about sustainable development of the planet (12.50).DiscussionThe study concludes that the Russian Federation is aligning its educational reforms with global trends in sustainable development. Educational programs in universities, focused on the environmental profile of training, should be aimed at highlighting the key environmental challenges in the country. Therefore, the socio-economic model of the new system of higher environmental education in the Russian Federation is taking place; it is relevant, timely set and has favorable prospects for its further development. In the end, the studied socio-economic model of the higher environmental education in the country can be risk-oriented. Therefore, it is highly recommended focusing on the further research and analysis of the potential risks that can limit the efficacy of the system functioning and evolution in the future.